Hastings Alumni Association-Fresno Chapter Luncheon Honoring Justice Donald Franson, Sr. - Watkins, Howard::::::::: (1988)
Judge Annette LaRue presenting to Justice Donald Franson, Sr. his plaque as the Chapter's 1988 Alumnus of the Year Hastings Dean Mary Kay Kane seated; Luncheon held at the Downtown Club